2017
DOI: 10.1371/journal.pone.0179753
|View full text |Cite
|
Sign up to set email alerts
|

Reef calcifiers are adapted to episodic heat stress but vulnerable to sustained warming

Abstract: Shallow marine ecosystems naturally experience fluctuating physicochemical conditions across spatial and temporal scales. Widespread coral-bleaching events, induced by prolonged heat stress, highlight the importance of how the duration and frequency of thermal stress influence the adaptive physiology of photosymbiotic calcifiers. Large benthic foraminifera harboring algal endosymbionts are major tropical carbonate producers and bioindicators of ecosystem health. Like corals, they are sensitive to thermal stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 45 publications
5
58
0
Order By: Relevance
“…Hallock et al (1995) demonstrated that onset of bleaching in Amphistegina consistently preceded maximum temperatures (see also Mendez-Ferrer et al, 2018). The response to acute photo-inhibition occurs within hours to days and to chronic stress over several days to a few weeks (Hallock et al, 1995(Hallock et al, , 2006aStuhr et al, 2017). These responses can be detected cytologically before visible loss of symbionts becomes evident .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Hallock et al (1995) demonstrated that onset of bleaching in Amphistegina consistently preceded maximum temperatures (see also Mendez-Ferrer et al, 2018). The response to acute photo-inhibition occurs within hours to days and to chronic stress over several days to a few weeks (Hallock et al, 1995(Hallock et al, , 2006aStuhr et al, 2017). These responses can be detected cytologically before visible loss of symbionts becomes evident .…”
Section: Discussionmentioning
confidence: 96%
“…The only parameter assessed at the sampling sites that appears problematic is temperature (means range between 28.8-31.7 • C), with only two of the means reported in Table 2 falling below 30 • C, and several exceeding 30.5 • C. Schmidt et al (2011) have shown that temperature effects are species-specific, and that a temperature above 31 • C has a negative effect on Amphistegina. Several authors have demonstrated that temperatures exceeding 30 • C significantly decrease photosynthetic activity in the diatom symbionts of LBF (Sinutok et al, 2011;Uthicke et al, 2012;Schmidt et al, 2016a, b;Stuhr et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that colonies exposed to moderate thermal stress are better conditioned to dealing with episodes of severe thermal stress (Oliver and Palumbi, 2011;Ainsworth et al, 2016). Thermal profiles showing a prebleaching spike in water temperatures, followed by a recovery period of cooler temperatures, prior to a hyperthermal event, reduced the severity of bleaching.…”
Section: Changes In Balance Among Host-compatible Symbiodiniaceae Durmentioning
confidence: 99%
“…Hallock (2000) summarized the potential and benefits of using reef-dwelling larger benthic foraminifers (LBF) as indicators of water quality conducive to coral-reef accretion. Experimental approaches have included studies of growth rates (Hallock, Forward & Hansen, 1986), photosynthetic activity (e.g., Talge & Hallock, 2003; Méndez-Ferrer, Hallock & Jones, 2018), prevalence of morphological anomalies (e.g., Prazeres, Uthicke & Pandolfi, 2016), symbiont loss (e.g., Hallock et al, 1995), and, most recently, proteomics (e.g., Prazeres et al, 2011; Stuhr et al, 2018) and antioxidant capacity (i.e., Prazeres, Uthicke & Pandolfi, 2016; Stuhr et al, 2017). …”
Section: Introductionmentioning
confidence: 99%